2015
DOI: 10.1007/978-3-319-18144-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Phosphinodithioate and Phosphoramidodithioate Hydrogen Sulfide Donors

Abstract: Hydrogen sulfide is rapidly emerging as a key physiological mediator and potential therapeutic tool in numerous areas such as acute and chronic inflammation, neurodegenerative and cardiovascular disease, diabetes, obesity and cancer. However, the vast majority of the published studies have employed crude sulfide salts such as sodium hydrosulfide (NaSH) and sodium sulfide (Na2S) as H2S "donors" to generate H2S. Although these salts are cheap, readily available and easy to use, H2S generated from them occurs as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 129 publications
2
48
0
1
Order By: Relevance
“…The need for slow-release H 2 S donor compounds was recognised since higher concentrations of the gas are toxic, the half-life of H 2 S is very short and simple salts like sodium hydrosulfide (NaSH) and sodium sulfide (Na 2 S) can only provide instantaneous H 2 S generation [43], [44], [45]. Anethole dithiolethione (ADT-OH) and 4-hydroxythiobenzamide (HTB) represent two simple moieties that release H 2 S slowly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for slow-release H 2 S donor compounds was recognised since higher concentrations of the gas are toxic, the half-life of H 2 S is very short and simple salts like sodium hydrosulfide (NaSH) and sodium sulfide (Na 2 S) can only provide instantaneous H 2 S generation [43], [44], [45]. Anethole dithiolethione (ADT-OH) and 4-hydroxythiobenzamide (HTB) represent two simple moieties that release H 2 S slowly.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 S is volatile and has short half-life in vivo , thus for long-term treatment its preferable to use donor molecules (prodrugs) that release H 2 S at a controlled rate. Several H 2 S donor compounds have been developed over the last couple of years and various H 2 S producing chemistries have been implicated but the control of H 2 S generation is still not perfect [43], [52], [53]. A further problem may arise from the side effects caused by the by-products that are formed during H 2 S release, thus in chronic diseases it is necessary to reduce the concentration of the donors as much as possible since very long treatment periods are anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…If the toxicity of H 2 S is primarily determined by its peak concentration, then one way of extending its therapeutic index would be to use slow-release donors; another potential direction may be to employ H 2 S donors that specifically target certain subcellular compartments (e.g. mitochondria); a further approach may involve multifunctional drugs where a H 2 S donating component is combined with a scaffold which has its own independent pharmacological actions (34,35). …”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of H 2 S-donating compounds have been described in the cardiovascular system [288, 289], urology [290], neuroinflammation [291], and ophthalmology [292]. These general areas have been thoroughly reviewed elsewhere [34, 109, 293].…”
Section: Modulation Of H2s Levels As a Strategy To Treat Cancermentioning
confidence: 99%
“…It should be noted that commercial preparations of GYY4137 are sold as a dichloromethane complex, and it has been reported that dichloromethane is metabolized to carbon monoxide (CO) [304, 305] an important gasotransmitter. Since CO is reported to have similar biological effects as H 2 S [306308], it is possible that some of the observed effects of GYY4137 could also be due, at least in part, to a contribution by CO [289]. …”
Section: Modulation Of H2s Levels As a Strategy To Treat Cancermentioning
confidence: 99%